2001
DOI: 10.1177/002087280104400404
|View full text |Cite
|
Sign up to set email alerts
|

Chinese corpus, western application

Abstract: Indigenization is a key issue in the development of professional social work in China. Chinese social work scholars have adopted the century-old conceptual formulation of ‘Chinese corpus, western application’ to balance the need for western knowledge and the need for intellectual autonomy. This article explores major current debates on ideology, teleology, epistemology and technology within the social work profession in the West and their implications for social work development in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(18 citation statements)
references
References 35 publications
(39 reference statements)
0
17
0
Order By: Relevance
“…The nature and context of indigenous knowledge has been the subject of substantial debate within the profession (Feng, 2014;Ferguson, 2005;Gray, 2008;Gray & Coates, 2010;Tsang & Yan, 2001;Yan & Cheung, 2006;Yunong & Xiong, 2011). However, although these debates are critical, they fall outside the remit of this article.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The nature and context of indigenous knowledge has been the subject of substantial debate within the profession (Feng, 2014;Ferguson, 2005;Gray, 2008;Gray & Coates, 2010;Tsang & Yan, 2001;Yan & Cheung, 2006;Yunong & Xiong, 2011). However, although these debates are critical, they fall outside the remit of this article.…”
Section: Introductionmentioning
confidence: 93%
“…These four frameworks can be found within the works of Dominelli (2002), Garrett (2013), Howe (1987) and Payne (1996). It is important to recognise here, once again, the dominance of Western-based knowledge and the need for increased indigenous contributions within social work ontological frameworks, as is indicated within the new global definition and the continued debate on indigenisation (Feng, 2014;Ferguson, 2005;Gray, 2008;Gray & Coates, 2010;Tsang & Yan, 2001;Yan & Cheung, 2006;Yunong & Xiong, 2011). As much as these perspectives are identified as being key international theoretical frameworks for the social work profession, as reflected in the SAGE Handbook of International Social Work (Lyons, Hokenstad, Pawar, Huegler, & Hall, 2012), their use is not uncontroversial.…”
Section: Ontological Frameworkmentioning
confidence: 99%
“…Several studies have then revealed that in multicultural and international encounters experienced by social workers and social work students, there is an unconscious regression to conservative and even nationalistic perspectives (Chambon 2013;Wiles 2013), leading to devaluing indigenous knowledge (Tsang & Yan, 2001). In addition, research findings show that the majority of international students express distress and experience cultural shock (Pyvis & Chapman, 2005;Zhou et al, 2008), at least at the beginning of their international sojourns, as a result of being far from their home culture (Belford, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gray and Fook (2004) argue that social work ought to celebrate and recognize commonalities in practice and simultaneously value and include differences, conceptualizing social work as a contextualized form of response to human need. While numerous authors (for example, Cox, 1995; Ferguson, 2005; Gray, 2005; Gray and Coates, 2010; Gray and Fook, 2004; Payne, 2001; Rankopo and Osei-Hwedie, 2011; Tsang and Yan, 2001) call for the indigenization of social work, and generally resist the dominance of the Western paradigm, there is less clarity about the ways in which this can be achieved. In this discussion, based on a small research project undertaken to consider the future directions of the field education program at the University of Papua New Guinea (hereafter UPNG), we will outline some particular opportunities that may manifest themselves in a range of contexts that may guide the indigenization project without compromising international standards for social work practice and social work education.…”
Section: Introductionmentioning
confidence: 99%